Kinerja Ekspor Indonesia: Dampak Pandemi COVID-19 vs Perang Rusia - Arifin, Samsul (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
Is COVID an obstacle to Indonesia’s trade flows vs. war to boost Indonesia’s exports? Application of the Gravity model using the OLS panel data fixed effect method to address the endogeneity problem for the 2018q1–2022q3 period. The significant positive results of exporters’ and importers’ GDP and the significant negatif results of distance prove the validity of the gravity model. The significant negatif results of the COVID-19 dummy and the significant positive results of the dummy war show that Indonesia’s exports with trading partners during COVID-19 have decreased, while the impact of the war was able to encourage an increase in international trade flows through increased imports to Indonesia. CAFTA will increase trading volume, but the effect will be insignificant. The potential to increase Indonesia’s exports going forward is in line with the end of COVID-19 and still the war.